THE INFLUENCE OF BRAND AWARENESS AND BRAND IMAGE ON PURCHASE INTENTION MEDIATED BY PERCEIVED VALUE AND BRAND TRUST AMONG USERS OF THE HAPPYFRESH E-COMMERCE PLATFORM IN JAKARTA - Jonathan, Darren; Tunjungsari, Hetty Karunia (International Journal of Application on Economics and Business, 2025)
In this study, brand awareness and brand image were tested for their influence on perceived value and brand trust toward customers' purchase intention. The research focused on users of the Happyfresh e-commerce platform in Jakarta, involving 215 samples. Data collected using a questionnaire instrument (G-form) was analyzed by the researchers using SmartPLS4 software. The findings revealed that all exogenous variables in this study significantly influenced through perceived value and brand trust toward customers' purchase intention. Perceived value and brand trust were also proven to be essential mediators in the relationship between all exogenous variables and the purchase intention of Happyfresh in Jakarta. Furthermore, the results showed that brand awareness positively and directly impacted purchase intention. However, brand image was found to have a positive but insignificant effect on purchase intention, indicating that while brand image plays an important role, it does not directly determine purchase intention without the support of competitive and consistent brand awareness. In addition to its contribution to academic literature, this study provides practical insights for Happyfresh regarding the importance of proper brand awareness in enhancing perceived value, brand trust, and sustainable purchase intention. On the other hand, brand image requires a more strategic, integrated, and sustainable approach to strengthen long-term relationships with customers.